2008
DOI: 10.1177/0363546508327561
|View full text |Cite
|
Sign up to set email alerts
|

Tension Level during Preconditioning Influences Hamstring Tendon Graft Properties

Abstract: The increased graft tension and stiffness could reduce postoperative knee laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
0
40
2
Order By: Relevance
“…However, the G4 is useful in cases of partial ACL rupture where it can augment the native ligament . It could be used in cases of isolated anteromedial bundle tears . It would be strong enough while also reducing the risk of impingement in the notch because of its smaller volume .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the G4 is useful in cases of partial ACL rupture where it can augment the native ligament . It could be used in cases of isolated anteromedial bundle tears . It would be strong enough while also reducing the risk of impingement in the notch because of its smaller volume .…”
Section: Resultsmentioning
confidence: 99%
“…All the grafts in the current study were preloaded before being pulled to failure. It has been shown that preloading during testing helps to reduce the loss of strength and stiffness that the tendon graft undergoes due to their viscoelastic properties . Tendons are temporarily prestrengthened when they undergo preconditioning .…”
Section: Discussionmentioning
confidence: 99%
“…Adding tensioning over a transferred tendon is a common practice to achieve ideal function. 13,14 Lieber 13 outlined how surgeons should determine tension to transferred tendons to optimize tendon excursion. Elias et al 14 reported that increasing the tension applied to hamstring tendon grafts during preconditioning decreases the postoperative loss of tension and stiffness due to viscoelasticity.…”
mentioning
confidence: 99%
“…13,14 Lieber 13 outlined how surgeons should determine tension to transferred tendons to optimize tendon excursion. Elias et al 14 reported that increasing the tension applied to hamstring tendon grafts during preconditioning decreases the postoperative loss of tension and stiffness due to viscoelasticity. Nevertheless, no research has been specifically directed to the appropriate tensioning of the tendon segment having direct end-to-end approximation.…”
mentioning
confidence: 99%
“…The authors subjected four commonly used grafts to a cyclic load of 89 N and showed no effect of the preconditioning compared to the no preconditioning condition on the anterior knee laxity. Analyzing the tension levels of quadruple-strand hamstring tendon graft preconditioned at 80 N and 160 N, Elias et al observed that increasing the tension on the graft board could decrease the postoperative loss of tension given by the viscoelastic behavior of the tendons [26]. Regarding the different force values proposed in these previous studies and the results regarding the mechanical graft tissue response, such as the residual anterior knee laxity after tensioning, it appears that simply applying a given force is not the best way of controlling graft tensioning.…”
Section: Discussionmentioning
confidence: 99%